PELANGGARAN ETIKA RANGKAP JABATAN NOTARIS DI MAKASSAR PERSPEKTIF SIYASAH JINAYAH - Haisyah,; Hisbullah, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
Violation of the ethics of concurrent notary positions is a polemic that raises a lot of debate in various circles and often becomes a hot topic of conversation. This study aims to determine the violation of the dual ethics of notary positions in Makassar from the perspective of siyasah jinayah. The type of research used is qualitative research (field research), data sources in the form of primary and secondary data obtained through observation, interviews, and documentation, in answering these problems the author uses a Normative Theology approach (shar'i) and Empirical Juridical approach. The results of this study indicate that: first, after going through the research there was no violation of the dual position of Notary in Makassar. The concurrent positions of Notary in Makassar generally serve as Lecturers and PPAT. However, the position is not a category of dual position prohibition contained in the Notary Position Law No. 2 of 2014 concerning Notary Position. Second, there is no finding of concurrent positions of Notary in Makassar, so far there has been no sanction for Notaries who concurrently hold positions. Sanctions against violations of concurrent Notary positions are in the form of severe sanctions, which lead to dishonorable dismissal along with the revocation of the SK by the Ministry of Law and Human Rights based on the procedure for enforcing sanctions for Notaries who violate the ethics of concurrent positions. In contrast to the sanctions for violating the dual position of Notary in Islam, in the form of Allah's wrath upon him. Because the Notary who commits a violation is the same as his denial of the oath of office.